2020
DOI: 10.1002/cbin.11344
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress induces Runx‐2 expression via upregulation of PIEZO1 in MC3T3‐E1 cells

Abstract: Mechanically induced biological responses in bone cells involve a complex biophysical process. Although various mechanosensors have been identified, the precise mechanotransduction pathway remains poorly understood. PIEZO1 is a newly discovered mechanically activated ion channel in bone cells. This study aimed to explore the involvement of PIEZO1 in mechanical loading (fluid shear stress)‐induced signaling cascades that control osteogenesis. The results showed that fluid shear stress increased PIEZO1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…24,46,47 Hence, the results provide evidence that osteogenesis of BMSC on 3D non-osteoinductive scaffolds can be induced solely by fluid flow in the absence of osteogenic supplements as reported in 2D systems where fluid effect is purely represented as shear stress. 14,15,19,20 Various types of bioreactors have been developed for bone tissue engineering. Each of the systems has distinctive features, and therefore, the identification of experimental parameters is the first step in reconciling the experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,46,47 Hence, the results provide evidence that osteogenesis of BMSC on 3D non-osteoinductive scaffolds can be induced solely by fluid flow in the absence of osteogenic supplements as reported in 2D systems where fluid effect is purely represented as shear stress. 14,15,19,20 Various types of bioreactors have been developed for bone tissue engineering. Each of the systems has distinctive features, and therefore, the identification of experimental parameters is the first step in reconciling the experimental data.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 46 , 47 Hence, the results provide evidence that osteogenesis of BMSC on 3D non-osteoinductive scaffolds can be induced solely by fluid flow in the absence of osteogenic supplements as reported in 2D systems where fluid effect is purely represented as shear stress. 14 , 15 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Yoneda et al found that Piezo1 activator Yoda1 triggers Ca 2+ influx and promotes proliferation in MC3T3-E1 osteoblasts in vitro [ 82 ]. In vitro, MC3T3-E1 osteoblasts required Piezo1 to adapt to the external mechanical fluid shear stress, thereby inducing osteoblastic Runx2 (Runt-related transcription factor 2) gene expression, partly through the AKT/GSK-3β/β-catenin pathway [ 83 ]. Recently, Wang et al have found a Piezo1-YAP1-collagen pathway in osteoblasts in vivo and in vitro [ 8 ].…”
Section: The Role Of Piezo Channels In Bonementioning
confidence: 99%
“…Different abnormalities or up/downregulation of cellular activities were observed in several studies following the silencing/blocking, deletion, cell specific or global knockout and deficiency of Piezo1. 9,[28][29][30][31][32][33] Since the recognition of Piezo1 &2 in 2010, they have been regarded as one of the most significant classes of mechanosensory proteins. It is now feasible to investigate the mechanism of Piezo1 engagement in physiological and pathophysiological processes as a result of recent developments in understanding their topology, the identification of the agonists Yoda1, Jedi1&2 as well as the antagonist GsMTx4, Ruthenium Red.…”
Section: Introductionmentioning
confidence: 99%